Statistical Investigation of ECG Signal of Sleep Apnea Patient (Global Journals of Research in Engineering, 2011)
The Hurst Exponent of the time series of a normal patient and apneal patient suggest that they are anti-persistent and the later has more self similarity compared to the former. It has been established that they are AR process and nonstationary. The Semblance analysis suggests strong correlation both positive and negative between them. Tentative mathematical models of the normal an apneal patient has also been suggested using Yule Walker method.
Keywords: Hurst exponent; ECG; autocorrelation; partial autocorrelation; Wavelet; Semblance